PENINGKATAN HASIL BELAJAR TEMATIK MELALUI PEMBELAJARAN ZOOM DENGAN MEDIA POWER POINT SISWA KELAS IV DI SD NEGERI 3 PECANGAAN JEPARA - Felicita Fadhilah (Tunas Nusantara, 2021)
This classroom action research was motivated by the low learning value of theme 8 sub-theme 2, during the Covid 19 pandemic this forced learning to be done online. The learning that was carried out initially used the whatapps group (WAG) media to convey all the lessons that were carried out by the teacher, but the results were not yet or still low. The purpose of this study was to determine the increase in student learning outcomes using zoom and power point media for grade IV students of SD Negeri 3 Pecangaan for the 2020/2021 academic year. This research was conducted in November 2020, at SD Negeri 3 Pecangaan. This type of research is Classroom Action Research with two cycles consisting of three meetings in one cycle, each cycle consisting of: planning, implementation, observation and reflection. Data collection techniques and tools in this study use descriptive analysis techniques for data in the form of work documents. students, score lists and observation sheets. The results showed that learning using power point media zoomn can create a pleasant learning atmosphere so that student learning outcomes increase, namely from the results of cycle I to cycle II there is an increase, in cycle 1 the number of students who got a complete score was 26 students or 68.42 % , the incomplete score in cycle 1 was 12 students or 31.58 %, while in cycle 2 there was an increase in the complete score, which was 37 students or 97.36 %, there was an increase of 28.94 %. It is concluded that learning using zoom and power ponit media can improve student learning outcomes.Key word: learning outcome, zoom learning, power point